A glance at the COVID-19 epidemic control system in Taiwan: implications for organizational crisis management and leadership in black swan events - Chuang, Szufang (International Journal of Human Resource Development Practice Policy & Research, 2024)
The COVID-19 pandemic caused substantial impacts and uncertainty in the world. For human resource leaders compelled into new roles in light of the pandemic, this paper used an exemplary case – Taiwan – to (1) discuss lessons and takeaways from the Taiwanese government’s and organizations’ response to the pandemic and (2) identify the structure of a pandemic control model and effective leadership behaviours at the national level that may be adopted in business settings to decrease the disruptive effects of a crisis. While efficient subsystems in organizational governance, policy, leadership, and culture are essential to combat a crisis, the evidence from Taiwan’s case in these contexts highlights the importance of various infrastructures and communication pathways in crisis management. The study aims to advance the understanding of effective responses and leadership skills in times of crisis and contribute to human resource literature and policy development in business settings. Human resource professionals and leaders play an important role as change agents to reduce the disruptive effects of a black swan event and can benefit from this study to be prepared for future crises. Implications for international human resource interventions in crisis management and leadership and recommendations for future research are provided.